Expressão imuno-histoquímica de células - tronco mesenquimais em lesões periapicais crônicas - Souza, Paulo Otávio Carmo (2019)
Introduction: Mechanisms of the pathogenesis process of chronic periapical lesions still require further discussion. Mesenchymal stem cells (MTC) present in the periapical region may participate in the process of genesis and development of chronic apical periodontitis, due to the ability of migration and differentiation in inflammatory environments. Objective: To evaluate the immunohistochemical expression of CTM markers (CD44, CD45, CD73 and CD105) in chronic periapical lesions. Method: Ten samples of periapical cysts and ten periapical granulomas were selected from the block file of the endodontic science laboratory of the Faculty of Dentistry of the Federal University of Goiás to perform an immunohistochemical reaction. The frequency of the presence or absence of the CD44, CD45, CD73 and CD105 markers was assessed under light microscopy in the fields of higher expression, and the immunohistochemical expression of CTM was determined when there was positive co-expression on the CD44, CD73 and CD105 markers and negative expression for the CD45 marker. The frequency of the qualitative variables were obtained and evaluated by the Chi-square test. Values of p <0.05 were considered significant. Results: In the periapical granulomas, 20% (2/10) presented co-expression for CTM positive markers (CD44, CD73 and CD105) associated with no expression for the CTM (CD45) negative marker. In the periapical cysts group there were no cases (0/10) of immunohistochemical coexpression for CD44, CD73 and CD105 markers associated with absence of CD45 expression. Conclusion: In the periapical cysts there was no immunohistochemical expression of CTM and the immunohistochemical expression occurred in 2 of the 10 cases of periapical granulomas.